DESAIN INTERIOR LOBI HOTEL SEBAGAI PHYSICAL SERVICESCAPE DALAM PEMBENTUKAN PLACE ATTACHMENT DAN REVISIT INTENTION - Jasmine Syahviarani; Mahendra Wardhana (Jurnal Arsitektur ARCADE, 2026)
Abstract: Hotel lobbies function as transitional spaces that play a crucial role in shaping initial impressions and spatial experiences through their interior design. In the context of hotel architecture and interior design, the lobby is one of the hotel's physical servicescape areas that can influence comfort, spatial perception, and emotional attachment to a place. The purpose of this study is to examine the role of hotel lobby interior design in the formation of place attachment and its relationship with revisit intention. The study was conducted using qualitative methods through a narrative literature review of various scientific sources relevant to the research topic. Thematic synthesis analysis aims to identify interior design elements that contribute to forming users' emotional connections with the hotel lobby. The results of the study indicate that the lobby interior design as a physical servicescape of the hotel can strengthen place attachment and has the potential to encourage revisit intention. This finding confirms that interior design not only functions as an aesthetic element, but also as a medium for forming spatial experiences that influence the emotional attachment of users in the context of hotel architecture and interiors. Keyword: Hotel Lobby Interior, Place Attachment, Revisit Intention Abstrak: Lobi hotel merupakan ruang transisi yang berperan penting dalam membentuk kesan awal dan pengalaman spasial melalui desain interiornya. Dalam konteks arsitektur dan interior perhotelan, lobi menjadi salah satu area physical servicescape hotel yang dapat mempengaruhi kenyamanan, persepsi ruang, dan keterikatan emosional pengunjung terhadap hotel secara keseluruhan. Tujuan penelitian ini adalah untuk mengkaji peran desain interior lobi hotel terhadap pembentukan place attachment serta kaitannya dengan revisit intention. Penelitian dilakukan dengan menggunakan metode kualitatif melalui kajian literatur naratif terhadap berbagai sumber ilmiah yang relevan dengan topik penelitian. Analisis sintesis tematik bertujuan untuk mengidentifikasi elemen desain interior yang berkontribusi dalam membentuk hubungan emosional pengguna dengan lobi hotel. Hasil kajian menunjukkan bahwa desain interior lobi sebagai physical servicescape hotel mampu memperkuat place attachment dan berpotensi mendorong revisit intention. Temuan ini menegaskan bahwa desain interior tidak hanya berfungsi sebagai elemen estetis, tetapi juga sebagai medium pembentuk pengalaman spasial yang mempengaruhi keterikatan emosional pengguna dalam konteks arsitektur dan interior perhotelan. Kata Kunci:  Interior Lobi Hotel, Place Attachment, Revisit Intention